Artificial intelligence and computer law, challenges and opportunities for current legislation - Reyna López , Gustavo Alberto (2025)
Artificial Intelligence is an aspect of modernity that has come to revolutionize all aspects of social life, including the legal field; In this presentation, we intend to explore its corners with computer law, analyzing how they challenge long-consolidated concepts and categories; also analyzing the specific impact of the challenges and opportunities they present for current legislation in the world; The primary objective of this document being to cover and summarize such a novel and broad topic, while making proposals that allow and encourage continuity in the development of its study; providing novel information and structured conclusions to the research carried out.